Sensory experience, sound and queerness in Chantal Akerman's Maniac Shadows (2013). (1st September 2019) - Fox, Albertine
This article offers the first scholarly study of Chantal Akerman's installation Maniac Shadows (2013). It argues that the deviating sensory strategies at work in this installation form part of a process of 'queering' that allows for the expression of queer forms of embodiment and pleasure. These queer tactics include sonic excess and spatial disintegration, skewed framing, haptic auditory perception and an emphasis on indeterminacy and ambiguity, primarily through the figure of the shadow. Drawing on Sara Ahmed's phenomenological approach to queerness, the article explores the sensuous queer effects arising from instances of audio-visual disorientation in Akerman's installation. It suggests that the centrality of shadows, combined with the amorphous soundscape and the presence of opaque images and oblique angles, produce jarring moments of strangeness that undermine notions of a stable unified subject and disrupt heteronormative space. Offering an alternative perspective on the autobiographical accounts of the installation that have emerged so far, the article suggests that Akerman's experimentation with spatial ambiguity is tied to a queerly inflected unravelling that pervades Maniac Shadows, as the artist fashions a less constricting and more subversive relational space for herself and her audience to grow into.